Proses Pembelajaran Di SD/MI Al-Ma'ruf Denpasar Pada Masa Pandemi Covid-19 (JURNAL ILMIAH SOSIOLOGI: SOROT, 2022)
The study, entitled Learning Process at SD/MI Al-Ma'ruf Denpasar During the Covid-19 Pandemic, analyzed the learning process at the elementary school level at grades I, II and III at MI Al-Ma'ruf Denpasar, then explained the impact positive and negative impacts of shifting the learning process before the pandemic and during the Covid-19 pandemic. The approach used in this research is an exploratory qualitative approach with an exploratory descriptive type, as well as an analysis using the theory of Diffusion of Technological Innovations by Evvert M. Rogers. The concept of innovation in this study states that there is a change in the learning process at MI Al-Ma'ruf Denpasar which in learning activities involves the role of parents, especially for grade I, II and III students. The learning process, which was originally carried out face-to-face, since the Covid-19 pandemic has been shifted to online learning from home using technology. The positive impact of the learning process during the Covid-19 pandemic at MI Al-Ma'ruf Denpasar is making teachers more creative in delivering learning, training the patience of teachers, students and parents. Established closeness between parents and children. While the negative impacts that occurred during the learning process during the Covid-19 pandemic had a direct impact on teachers, students and parents, namely the level of student understanding was lacking, eye health was disturbed, students did not focus on learning and social development was not well established. In this case, students not only get the attention of the teacher in the learning process, but the role of parents in supervising learning at home becomes very important when carrying out the learning process during the Covid-19 pandemic. Keywords: Online Learning, Pandemic Covid-19, MI Al-Ma’ruf Denpasar